Modification of the existing maximum residue levels for fenazaquin in strawberries, sweet peppers, tomatoes and aubergines - European Food Safety Authority (EFSA); Giulia Bellisai; Giovanni Bernasconi; Luis Carrasco Cabrera; Irene Castellan; Monica delAguila; Lucien Ferreira; Luna Greco; Samira Jarrah; Renata Leuschner; Andrea Mioč; Stefanie Nave; et al. (EFSA Journal, 2025)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Gowan Crop Protection Limited submitted a request to the competent national authority in Italy to modify the existing maximum residue levels (MRLs) for the active substance fenazaquin in strawberries, sweet peppers, tomatoes and aubergines. The data submitted in support of the request were found to be sufficient to derive MRL proposals for the requested commodities. Adequate analytical methods for enforcement are available to control the residues of fenazaquin on the commodities under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues of fenazaquin and its toxicologically relevant plant metabolite 2‐(4‐tert‐butylphenyl)ethanol (TBPE) resulting from the use of fenazaquin according to the reported agricultural practices is unlikely to present a risk to consumer health. The consumer risk assessment shall be regarded as indicative and affected by uncertainties pending the assessment of the data gaps identified in the review of the existing MRLs and due to the limited information on TBPE residue concentrations associated to existing CXLs implemented as EU MRLs in the EU legislation.